1998
DOI: 10.1159/000023172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cell Density on Hormonal Secretion from Human Pituitary Adenomas in vitro

Abstract: Cell density effects were investigated on tumorous hormonal secretion from 10 pituitary adenomas: 3 somatotrophinomas secreting GH and PRL; 7 gonadotrophinomas, 3 co-secreted both FSH and LH, all 7 secreted LH. Enzymatically dispersed tissue was plated out in 24-well plates at 5 ×105, 105, 5 ×104 and 104 cells/well in serum-free media. Media were collected weekly for 2 weeks. Results: In 3 of 3 somatotrophinomas, GH and PRL secretion was higher (p < 0.05) at both wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The anterior pituitary gland is sensitive, in a dose-dependent fashion, to the effects of iron overload from transfusions [4] . Studies of human anterior pituitary adenomas showed that gonadotropes require more iron as compared with other pituitary cell types [5] . Thus, these cells are most affected, resulting in declining synthesis of luteinizing hormone (LH) and follicle-stimulating hormone (FSH).…”
Section: Introductionmentioning
confidence: 99%
“…The anterior pituitary gland is sensitive, in a dose-dependent fashion, to the effects of iron overload from transfusions [4] . Studies of human anterior pituitary adenomas showed that gonadotropes require more iron as compared with other pituitary cell types [5] . Thus, these cells are most affected, resulting in declining synthesis of luteinizing hormone (LH) and follicle-stimulating hormone (FSH).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence and severity of hypogonadism in thalassemia major varies among studies, depending on the age group studied, genotype of thalassemia [17,18], extent of transfusion, age at the beginning and type of iron chelation therapy [18,19].The anterior pituitary gland is sensitive, in a dose-dependent fashion, to the effects of iron overload from transfusions [20]. Studies of human anterior pituitary adenomas showed that gonadotropes require more iron as compared with other pituitary cell types [21]. Thus, these cells are most affected, resulting in declining synthesis of luteinizing hormone (LH) and follicle-stimulating hormone (FSH).…”
Section: Discussionmentioning
confidence: 99%
“…NTBI is also a catalyst for the formation of reactive oxygen species, causing oxidative damage [1]. Studies of human anterior pituitary adenomas showed that gonadotropes require more iron as compared with other pituitary cell types [2]. Thus, these cells are most affected, resulting in declining synthesis of luteinizing hormone (LH) and follicle-stimulating hormone (FSH).…”
Section: Introductionmentioning
confidence: 99%